JAK2 as a Molecular Marker in Myeloproliferative Diseases - R. Mata; D. Subira; A. Garcia-Raso; P. Llamas (Cardiovascular & Hematological Agents in Medicinal Chemistry, 2007)
The molecular pathogenesis of the myeloproliferative disorders (MPD) is poorly understood, except for chronic myeloid leukemia (CML). Recently, several groups have discovered a novel recurrent unique acquired clonal mutation in a tyrosine-kinase JAK2 in patients with Philadelphia-negative MPD and other myeloid disorders. It consists in a guanineto- thymine change encoding a valine to phenylalanine at codon 617 (JAK2 V617F). JAK2 and the other members of the Janus kinase family are tyrosine kinases that function as intermediates between membrane receptors and intracellular signalling molecules. The mutation occurs within the enzymatically inactive JH2 pseudo-kinase domain that regulates the active JH1 kinase domain. The JAK2 activation leads to constitutive JAK and STAT (activators of transcription) hyperactivation with induction of growth factor hypersensitivity and cell transformation. Some authors have found a higher risk of vascular thrombosis and higher platelet activation when the mutation is present. Therefore, the JAK2 mutation offers a molecular target for new drugs investigation in a similar way to bcr/abl rearrangement in CML. For all these reasons, several studies related to JAK2 have arisen in the last year. In this report, we will review the literature and discuss its possible clinical and prognostic significance.
Keywords: Myeloproliferative diseases